Sphere P acking Bound for E-capacity of Secrecy Leakage of the Broadcast Channel With Confidential Messages - Afshar, Nasrin (Mathematical Problems of Computer Science, 2021)
The discrete memoryless broadcast channel with confidential messages (BCC) involves two discrete memoryless channels with two sources and one encoder. A common message must be transmitted to two receivers and a private message to the intended receiver, while keeping the other receiver as ignorant of it as possible. Secrecy leakage rate is the rate of information available to the unintended receiver about the private message. Upper bound for E-capacity of secrecy leakage of the BCC is derived.